Hydrodynamic Response to Current and Wind on a Large Floating Interconnected Structure - Sarat Chandra Mohapatra; Pouria Amouzadrad; Iuri Baldaconi da Silva Bispo; C. Guedes Soares (Journal of Marine Science and Engineering)
A numerical hydrodynamic model for a moored interconnected floating large structure under the action of regular waves is presented to analyze the effect of current and wind. The floating structure consists of 20 hinged plates that are linked together and secured with mooring lines along its edges. A brief discussion is provided on the multi-body hydrodynamics equations related to the numerical model definitions in both the frequency and time domains. Conversely, a concise overview of the experiment is given. The numerical model outcomes of vertical displacements and wave quantities are compared against the results obtained from model test data sets and numerical and analytical models in a recent publication. A high degree of accuracy has been noted in reflection and transmission coefficients with a certain value of current velocity. The numerical model simulating interconnected structures of 10 and 16 hinged plates is analyzed, and the resulting vertical displacements under the influence of current are compared to those of a 20-hinged structure. The impact of currents and winds on the hydrodynamic response of the structure is examined by studying various results, using stiffness values for both mooring and hinges. Further, the effect of wavelengths on the wave transmission on every side of the interconnected structure through contour diagrams, hydrodynamic diffraction for different incident angles, and wave quantities on current speed are analyzed. It is observed that as the current speed rises, the structural displacement also escalates; meanwhile, no impact of the wind on the floating interconnected structure is noted. It has been observed that as the wave direction shifts from 0° to 60°, the interconnected floating structure experiences a slight reduction in wave motion throughout the entire system.